Surveillance of antimicrobial resistance in veterinary medicine in the United States: Current efforts, challenges, and opportunities - Ruzante, Juliana M.; Harris, Beth; Plummer, Paul; Raineri, Raissa R.; Loy, John Dustin; Jacob, Megan; Sahin, Orhan; Kreuder, Amanda J. (Frontiers in Veterinary Science, 2022)
Antimicrobial resistance (AMR) is a global problem facing human, animal, plant, and environmental health by threatening our ability to effectively treat bacterial infections with antimicrobials. In the United States, robust surveillance efforts exist to collect, analyze, and disseminate AMR data in human health care settings. These tools enable the development of effective infection control methods, the detection of trends, and provide the evidence needed to guide stewardship efforts to reduce the potential for emergence and further spread of AMR. However, in veterinary medicine, there are currently no known equivalent tools. This paper reviews efforts in the United States related to surveillance of AMR in veterinary medicine and discusses the challenges and opportunities of using data from veterinary diagnostic laboratories to build a comprehensive AMR surveillance program that will support stewardship efforts and help control AMR in both humans and animals